A Novel DTC Method with Efficiency Improvement of IM for EV Applications - Aygun, H.; Aktas, M. (Engineering, Technology & Applied Science Research, 2018)
Induction motor (IM) stator flux optimization is very important in order to get increasing running distance per battery charge of electric vehicles (EVs). This study introduces a new direct torque control (DTC) method for efficiency improvement of IM in EV applications. Also, it is proposed to decrease the torque ripple of DTC based IM. Generally, loss minimization algorithms can be simplified by neglecting the core loss or the effect of leakage inductance in the motor model. However, neglecting the core loss causes an error in torque control of DTC. Beside this, exact loss minimization cannot be achieved since a large voltage drop across leakage inductance occurs especially in high-speed region. In the proposed method, the motor model is simplified by neglecting the current in the core loss resistance branch instead of neglecting the core loss and the effect of leakage inductance. The proposed method is simulated in Matlab for variable speeds and loads. Results show that it provides a significant reduction of losses and decreases the torque ripple of IM drives.